Assessing the vitality of a local Chinese community language: Cantonese in Ipoh, Malaysia - Zhou, Wei; Ang, Lay Hoon (SAGE Publications, 2024)
Malaysia is a multilingual and multiethnic country with a substantial population of ethnic Chinese, who use standardized languages such as Malay, English, and Mandarin, as well as various Chinese dialects in their daily lives within and beyond Chinese communities. Cantonese is a community language that significantly impacts the lives of local Chinese in the city of Ipoh, Malaysia. This study aims to examine the vitality of Cantonese in Ipoh using the language vitality and endangerment (LVE) tool developed by UNESCO. Nine LVE-proposed factors reflecting the degree of endangerment were investigated. Using a survey method, 377 participants from various groups were randomly selected from the Chinese community in Ipoh, Malaysia during January 6 to February 5, 2022. The result shows that Cantonese in Ipoh is rated as “Unsafe,” indicating that measures should be taken to prevent its further decline. The result suggests that further research is needed to gain a clearer understanding of the factors affecting language shift and maintenance, as well as the potential and challenges of linguistic and cultural diversity in the contemporary world.